2002
DOI: 10.2337/diacare.25.4.684
|View full text |Cite
|
Sign up to set email alerts
|

Does Diabetes Disease Management Save Money and Improve Outcomes?

Abstract: OBJECTIVE -Little is known about the impact of disease management programs on medical costs for patients with diabetes. This study compared health care costs for patients who fulfilled health employer data and information set (HEDIS) criteria for diabetes and were in a health maintenance organization (HMO)-sponsored disease management program with costs for those not in disease management.RESEARCH DESIGN AND METHODS -We retrospectively examined paid health care claims and other measures of health care use over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 38 publications
(13 reference statements)
2
74
0
4
Order By: Relevance
“…We assumed that annual program costs for each enrolled patient would be $424, based on an estimate of costs from prior studies of diabetes quality improvement programs. 23,24 Additionally, with the program in place, the cost of diabetes care related to preventive medications and routine testing would increase by $600 per patient annually based on a micro-costing exercise, 25 thereby bringing the to- tal annual cost per patient to $1,024. Based on the peer-reviewed literature, we assumed that the intervention would lead to multiple improvements in diabetes care.…”
Section: Policy Projectionsmentioning
confidence: 99%
“…We assumed that annual program costs for each enrolled patient would be $424, based on an estimate of costs from prior studies of diabetes quality improvement programs. 23,24 Additionally, with the program in place, the cost of diabetes care related to preventive medications and routine testing would increase by $600 per patient annually based on a micro-costing exercise, 25 thereby bringing the to- tal annual cost per patient to $1,024. Based on the peer-reviewed literature, we assumed that the intervention would lead to multiple improvements in diabetes care.…”
Section: Policy Projectionsmentioning
confidence: 99%
“…The impact of lowering A1c on medical costs is mixed. [36][37][38][39][40][41] The recently reported outcomes of the Medicare Health Support Disease Management Pilot Program, which enrolled more than 100,000 individuals with diabetes in the intervention and approximately 60,000 in the control group, showed no evident reduction in the utilization of acute care or the cost of care. 42 DSME is typically performed by diabetes educators and is a covered benefit by Medicare and many commercial payers.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…In fact, diabetes is the most frequently included condition among DM program offerings. While numerous studies have demonstrated the ability of DM to decrease A1c levels, 3,10 there are few analyses of the impact of DM on the frequency of A1c testing in a large population.…”
Section: Introduction Dmentioning
confidence: 99%
“…[2][3][4][5] The Diabetes Control and Complications Trial (DCCT) found that persons receiving intensive insulin treatment to reach a glycemic goal of 6.05% or less had dramatic relative reductions in risk for microvascular and neurological end points, including greater than 70% reduction for clinically important sustained retinopathy, 56% for laser photocoagulation, 39% for microalbuminuria, and 60% for confirmed clinical neuropathy. Although they did not reach statistical significance, specific macrovascular end points realized an approximate 41% risk reduction for combined macrovascular events.…”
Section: Introduction Dmentioning
confidence: 99%